Sosialisasi Produk Pembiayaan Mudharabah untuk Meningkatkan Literasi Keuangan Syariah pada Masyarakat di Desa Mlarak Kabupaten Ponorogo - Fauzi, Moh. Ihsan; Nuhaa, Muhamad Afif Ulin; Firmansyah, Yuro Bintang (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
BMT has an important role in helping the needs of the community related to access to capital in business activities with mudharabah financing products. However, the lack of public knowledge and understanding of Islamic finance causes public interest in accessing capital through BMT is still minimal. Especially with the assumption of the public that BMT is the same as other conventional financial institutions. This research aims to provide understanding and knowledge related to mudharabah financing products to the people of Mlarak Village, Ponorogo Regency, especially people who have UMKM. The method used in the socialization of mudharabah financing products is a lecture by delivering explanations related to mudharabah financing products and questions and answers or discussions related to access to capital needed by the community. The results of this study show that the public increasingly knows and understands the advantages of mudharabah financing products in providing access to capital to the community and shows interest in accessing mudharabah financing products at BMT for capital needs in their business activities.